(untitled) (Journal of the College of Basic Education, 2022)
The discourse of the theatrical performance is formed through the process of interaction that occurs between the total elements of building and installing the scenes of the show and the recipient who interacts with the visual and audio system, to result in this interaction a general framework for the meaning that the show seeks to transmit to the recipient, so if the theatrical show is a representation of the mentally lived reality Visually, the show in this sense will be in a way a reproduction of life, through “reducing the image of reality at the level of size, area, color and angle. This means that the theater is only a miniature image of reality or life, and the auditory and other components overlap in this image. visual" ( )